Strangeness from 20AGeV to 158AGeV - Alt, C.; Antičić, Tome; Baatar, B. Barna, D, Bartke, J.; Behler, M. Betev, L.; Bialkowska, H. Billmeier, A.; Blume, C. Boimska, B.; Botje, M. Bracinik, J.; Bramm, R. Brun, R.; Bunčcić, P. Cerny, V.; Christakoglou, P. Chvala, O.; Cramer, J.G. Csato, P.; Dinkelaker, P. Eckardt, V.; et al. (2004)
New results from the energy scan programme of NA49, in particular kaon production at 30AGeV and fi production at 40 and 80AGeV are presented. The K+/pi+ ratio shows a pronounced maximum at 30AGeV ; the kaon slope parameters are constant at SPS energies. Both findings support the scenario of a phase transition at about 30AGeV beam energy. The fi/pi ratio increases smoothly with beam energy, showing an energy dependence similar toK-/pi-. The measured particle yields can be reproduced by a hadron gas model, with chemical freeze-out parameters on a smooth curve in the T– &micro ; ; ; ; _B plane. The transverse spectra can be understood as resulting from a rapidly expanding, locally equilibrated source. No evidence for an earlier kinetic decoupling of heavy hyperons is found.
Projekt MZOS
ENG